Evaluation of Anti-Hyperuricemic Potential of Fumaria Indica Extract on Xanthine Oxidase Activity in Vitro - Navida Manzoor, Azka Khan, Samra Suleman, Mahreen Akhtar, Qura-Tul-Ain, Naseem Saud (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: A metabolic condition called hyperuricemia is caused by increased uric acid levels, which can range from 6.6 to 7.6.Treatment for hyperuricemia is, low protein diet and drugs like allopurinol and Febuxostat. Medicinal plants and herbs Top of Form are safer, almost completely nontoxic, and less likely to cause adverse effects than medications. Fumaria Indica (indica) a Herb belongs to family (Fumariaceae), was chosen to evaluate its Invitro uric acid lowering activity. Objective: To evaluate the effect of Fumaria indica extract on xanthine oxidase activity in vitro. Method: The study was designed to evaluate the xanthine oxidase inhibitory activity of Fumaria indica extract might inhibit xanthine oxidase in vitro. The inhibitory activity of xanthine oxidase in vitro was evaluated spectrophotometrically at 295nm using a UV/VIS spectrophotometer. The inhibitory concentration was estimated using the EZ fit enzyme kinetics tool. Results: Fumaria indica dramatically reduced uric acid generation. FIE inhibited xanthine oxidase by 80% at 100 g/ml, but febuxostat inhibited it by 97.50% at the same concentration. The inhibitory concentration was determined using the EZ Fit enzyme kinetics test. FIE and febuxostat had IC50s of 12.59g/ml and 9.30g/ml, respectively. Conclusion:The observed results indicate that fumaria indica extract could be a viable source for the development of novel XOI. FIE, based on its toxicity profile and uric acid reducing action, can be used to treat hyperuricemia and other hyperuricemia-related disorders, particularly gout. Keywords: febuxostat, Fumaria indica ,Invitro, uric acid .